2014
DOI: 10.1002/bem.21836
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception and public concerns of electromagnetic waves from cellular phones in Korea

Abstract: In this study, the difference between the risk perception of electromagnetic waves from cellular phones and the risk perception of other factors such as environment and food was analyzed. The cause of the difference in the psychological and social factors that affect the group with high risk perception of electromagnetic waves was also analyzed. A questionnaire survey on the risk perception of electromagnetic waves from cellular phones was carried out on 1001 subjects (men and women) over the age of 20. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…A lower level of trust in government policies was also associated with an increased risk perception of EMF sources [van Dongen et al, 2013]. Furthermore, Kim et al [2014] revealed that people who gave higher ratings on "personal knowledge" and "seriousness of the risk to future generations" also exhibited increased risk perception of EMF from mobile phones. Factors associated with decreased risk perception of EM waves from 5G network base stations were also identified.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A lower level of trust in government policies was also associated with an increased risk perception of EMF sources [van Dongen et al, 2013]. Furthermore, Kim et al [2014] revealed that people who gave higher ratings on "personal knowledge" and "seriousness of the risk to future generations" also exhibited increased risk perception of EMF from mobile phones. Factors associated with decreased risk perception of EM waves from 5G network base stations were also identified.…”
Section: Discussionmentioning
confidence: 94%
“…And Kowall et al [2012] reported that female gender, a higher level of education, visibility of mobile phone base stations, and a higher level of negative emotions were associated with increased risk perception of mobile phone base stations. Furthermore, Kim et al [2014] found that higher ratings on a few risk characteristics such as "personal knowledge," "outrage," and "seriousness of the risk to future generations" were associated with increased risk perception of mobile phones.…”
Section: Introductionmentioning
confidence: 99%
“…There are public concerns for potential health effects caused by the use of RF-EMF associated technologies, mobile phones and base stations (Kim et al, 2014;Tjong et al, 2015;Wiedemann et al, 2014). Furthermore, there is currently a strong need for quantification of personal exposures using objective measures for current and future human epidemiological studies (van Deventer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For personal use only, all rights reserved. and investment products (Duff 2014, Kim et al 2014, Morris 2011, Ngo et al 2013, Portell et al 2014, Sachse et al 2012, Wang et al 2011.…”
Section: Factor Analysis Of Risk Characteristicsmentioning
confidence: 99%